قضية اللباس في المجتمع الجزائري بين الحداثة والقيم - مسعودي, عمر; رقيق, عبد الكريم (جامعة الوادي - University of Eloued, 2018)
إن البحث في ظاهرة اللباس في المجتمع الجزائري، في ثباته وتغيره، يتناول في الدرجة الأولى العلاقة بين المجتمع والدين؛ المجتمع باعتباره مصدر العادات والتقاليد التي تعبر عنها تجليات متعددة في السلوك اليومي، ومن تلك العادات ظاهرة اللباس وتغيراته المرتبطة بظروف العصر، والدين باعتباره يفرض أشكالاً متعددة في اللباس على المرء التقيد بها ، غير أنه قد ظهر بعض أنصار الفكر الحداثي في المجتمعات الإسلامية أصحاب صبغة الفكر التجديدي ،يتبنون بعض النظريات الغربية، الداعية للثورة على تلك القيم الدينية والعادات الاجتماعية من أجل موكبة العصر ، ويعد اللباس من مقدمات القيم الدينية والعادات الاجتماعية التي طالتها موجة التغيير الحداثي. Abstract: The study of the phenomenon of dress in Algerian society, in its stability and change, deals primarily with the relationship between society and religion; society as a source of customs and traditions expressed by various manifestations in daily behavior, such customs dress phenomenon and its changes related to the circumstances of the times, religion as imposing forms But some modernist thinkers have emerged in the Arab societies who have the tincture of regenerative thought, adopting some Western theories, calling for a revolution on those religious values and social customs for the procession of the age, and preparing the dress from introductions Religious values and social customs that have been affected by the wave of modern change.
مقال
Keywords: اللباس ، الحداثة ، القيم; dress, modernity, values